Does Confucian culture affect public service motivation of grassroots public servants? Evidence from China - Duan, Cheche; Jiao, Jiaxin; Zhao, Chunzhen; Li, Yingying (Frontiers in Psychology, 2023)
Public service motivation contains distinctive cultural characteristics. Different cultural backgrounds shape public service motives with different connotations and levels. However, the traditional cultural values rooted in historical development and socialization process have not received enough attention in the research on public service motivation. In order to investigate the influence of Confucian culture based on Chinese scenes on public service motivation, in the current study we collected 1308 representative questionnaires from 12 cities in central and eastern China, and adopted the dual fixed effect model and moderating effect model to verify six hypotheses. The empirical results showed that Confucian culture has different effects on public service motivation from four dimensions, namely, attraction to politics and policy making (APP), commitment to public interest (CPI), compassion (COM), and self-sacrifice (SS). The paternalistic leadership plays a part in moderating the influence of Confucian culture on public service motivation. This study not only expands the cross-cultural applicability of the theory of public service motivation in non-western countries, but also supplements the evidence of research on public service motivation in East Asian countries. In practice, it is necessary for the organizations to consider the importance of specific cultural values for organizational culture and personal value orientation.